Oral feeding with polyunsaturated fatty acids fosters hematopoiesis and thrombopoiesis in healthy and bone marrow-transplanted mice - Limbkar, Kedar; Dhenge, Ankita; Jadhav, Dipesh D.; Thulasiram, Hirekodathakallu V.; Kale, Vaijayanti; Limaye, Lalita (Journal of Nutritional Biochemistry, 2017)
Hematopoietic stem cells play the vital role of maintaining appropriate levels of cells in blood. Therefore, regulation of their fate is essential for their effective therapeutic use. Here we report the role of polyunsaturated fatty acids (PUFAs) in regulating hematopoiesis which has not been explored well so far. Mice were fed daily for 10 days with n-6/n-3 PUFAs, viz. linoleic acid (LA), arachidonic acid (AA), alpha-linolenic acid and docosahexanoic acid (DHA) in four separate test groups with phosphate-buffered saline fed mice as control set. The bone marrow cells of PUFA-fed mice showed a significantly higher hematopoiesis as assessed using side population, Lin-Sca-1(+)ckit+, colony-forming unit (CFU), long-term culture, CFU-spleen assay and engraftment potential as compared to the control set. Thrombopoiesis was also stimulated in PUFA-fed mice. A combination of DHA and AA was found to be more effective than when either was fed individually. Higher incorporation of PUFAs as well as products of their metabolism was observed in the bone marrow cells of PUFA-fed mice. A stimulation of the Wnt, CXCR4 and Notch1 pathways was observed in PUFA-fed mice. The clinical relevance of this study was evident when bone marrow-transplanted recipient mice, which were fed with PUFAs, showed higher engraftment of donor cells, suggesting that the bone marrow microenvironment may also be stimulated by feeding with PUFAs. These data indicate that oral administration of PUFAs in mice stimulates hematopoiesis and thrombopoiesis and could serve as a valuable supplemental therapy in situations of hematopoietic failure. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: Bone Marrow Transplantation (Bmt); Cord Blood; Down-regulation; Ex-vivo Expansion; Hematopoiesis; Hematopoietic Stem Cells (Hscs); Lipid rafts; Myocardial-infarction; Polyunsaturated Fatty Acids; Progenitor Cells; Prostaglandin-e2; Self-renewal; Spleen Colonies; Stem-cell Proliferation; Thrombopoiesis